FCGBP promotes ovarian cancer progression via activation of IL-6/JAK-STAT signaling pathway - Zhiqin Fu; Kelie Chen; Fang Zheng; Wangang Gong; Ding Chao; Chao Lu (Journal of Translational Medicine)
Abstract Background Ovarian cancer is among the deadliest gynecological malignancies, primarily due to late-stage diagnosis and poor prognosis. Novel biomarkers and therapeutic targets are urgently needed to enhance early detection and treatment efficacy. Fc fragment of IgG-binding protein (FCGBP), a mucin-like glycoprotein, has been associated with various cancers, but its specific role in ovarian cancer progression has not been well-defined. This study aimed to investigate the clinical relevance, functional role, and underlying mechanisms of FCGBP in ovarian cancer progression. Methods Gene expression profiles from multiple public datasets were analyzed to identify differentially expressed genes. Weighted gene co-expression network analysis was performed to correlate FCGBP expression with clinical traits. Single-cell RNA sequencing and pseudotime trajectory analyses were used to examine FCGBP expression dynamics. FCGBP expression was validated in ovarian cancer tissues using quantitative PCR, western blotting, and immunohistochemistry. Functional assays, including proliferation, migration, invasion, and colony formation, were conducted in SKOV3 and ES-2 ovarian cancer cell lines with FCGBP knockdown. The molecular mechanism was explored using dual-luciferase reporter assays and co-immunoprecipitation. Enzyme-linked immunosorbent assays and western blotting assessed cytokine levels and pathway activation. An in vivo xenograft mouse model was used to evaluate tumorigenic effects. Results FCGBP expression was significantly elevated in ovarian cancer tissues and correlated with advanced tumor stage and poor prognosis. Single-cell analysis showed FCGBP expression peaked in terminally differentiated epithelial cancer cells. Silencing FCGBP significantly reduced proliferation, migration, invasion, and colony formation in vitro, and suppressed tumor growth and improved survival in vivo. Mechanistically, FCGBP enhanced interleukin-6 expression by interacting with NF-kappaB subunit p65, leading to activation of the JAK-STAT signaling pathway. Rescue experiments confirmed that exogenous interleukin-6 could restore the tumor-promoting effects lost upon FCGBP knockdown. Conclusions Our findings establish FCGBP as a crucial oncogenic regulator in ovarian cancer, acting through the IL-6-mediated activation of the JAK-STAT signaling pathway. FCGBP holds promise as a novel diagnostic biomarker and therapeutic target, potentially improving early diagnosis, prognosis, and management of ovarian cancer.